Sistem Keamanan di Maneuvering Area bandar Udara Domine Eduard Osok Sorong - Bahrawi, Ahmad (Politeknik Penerbangan Makassar, 2020)
Domine Eduard Osok Sorong Airport, which is located close to the community settlement of Sorong, causes the airport to have a higher level of vigilance. Which is the presence of pedestrians, animals, and runway users as road access which makes it an obstruction for air traffic guides and pilots and for airport security. This study covers the scope of combine service where only one unit works and only uses one frequency, namely tower units where ATC is fully responsible for regulating air traffic from ground to fl245 height. This condition is applied to save costs and further streamline the work where traffic in Sorong is not as crowded as before the pandemic. Security conditions at Maneuvering Area of Domine Eduard Osok Airport are still lacking and not standard. Many residents around the airport often cross the runway without getting permission from the patrol and ATC both pedestrians and those using motor vehicles. There is still a lack of efficient patrol guarding of people who want to cross the runway because, the patrol is not at any time in place. Solving the problem by conducting flight safety socialization to residents who live in the area around the airport then invite some community leaders to tour the airport and build a post for patrols around the runway 27 area. Create a crossbar or install Traffic light around the runway 27 area that is often used by residents to cross the runway.